2013
DOI: 10.1007/s00296-013-2876-z
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of psoriatic arthritis in dermatological patients with psoriasis: a cross-sectional study

Abstract: The exact prevalence of psoriatic arthritis (PsA) among patients with psoriasis is still not conclusive. Data in the literature vary between 5.8 and 30 %. Objective of this study was to gain more information on the prevalence of PsA among patients with psoriasis in Germany. Between 09/2010 and 05/2011, consecutive patients from dermatological private practices and a university hospital with psoriasis were asked to fill out the validated German Psoriatic Arthritis Diagnostic (GEPARD) Questionnaire. Patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 22 publications
1
42
0
4
Order By: Relevance
“…In 7 of 12 studies, the final diagnosis was made by a senior rheumatologist 2,12,[15][16][17]21,22 ; in the 5 other studies, it was not stated who was responsible for the final diagnosis of PsA. 13,14,[18][19][20] CASPAR, GRAPPA, Moll and Wright criteria, as well as the rheumatologists' assessments were used to make the final diagnosis of PsA (Table I). When considered, in 1 study, 2 laboratory tests and imaging results did not markedly alter the prevalence of PsA based on the rheumatologists' assessment of medical history and clinical examination alone.…”
Section: Resultsmentioning
confidence: 99%
“…In 7 of 12 studies, the final diagnosis was made by a senior rheumatologist 2,12,[15][16][17]21,22 ; in the 5 other studies, it was not stated who was responsible for the final diagnosis of PsA. 13,14,[18][19][20] CASPAR, GRAPPA, Moll and Wright criteria, as well as the rheumatologists' assessments were used to make the final diagnosis of PsA (Table I). When considered, in 1 study, 2 laboratory tests and imaging results did not markedly alter the prevalence of PsA based on the rheumatologists' assessment of medical history and clinical examination alone.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for this discrepancy could be the geographical variation in PsA. Europe and North America present higher PsA prevalence ranging between 20.6% to 30% compared with Asia where PsA is significantly lower (8.7%) as seen in a large study of 1149 patients . The data from South America are conflicting.…”
Section: Discussionmentioning
confidence: 96%
“…[2][3][4] An estimated 20---30% of psoriasis patients may develop PsA. 5,6 Imaging studies have demonstrated the existence of considerable number of patients with psoriasis and undiagnosed PsA, a reflection of the presence of subclinical arthritic disease in clinically normal joints. 7,8 Persistent joint inflammation can lead to bone damage, and it is estimated that half of PsA patients develop irreversible joint lesions within the first few years of disease.…”
Section: Introductionmentioning
confidence: 99%